Research data warehouse best practices: catalyzing national data sharing through informatics innovation. - Murphy, Shawn N; Visweswaran, Shyam; Becich, Michael J; Campion, Thomas R; Knosp, Boyd M; Melton-Meaux, Genevieve B; Lenert, Leslie A (Journal of the American Medical Informatics Association, 2022)
Research Patient Data Repositories (RPDRs) have become essential infrastructure for traditional Clinical and Translational Science Award (CTSA) programs and increasingly for a wide range of research consortia[[1], [3]] and learning health system networks. In the data commons, datasets associated with various research projects were made findable, accessible, interoperable, and reusable (FAIR) through the open-source Gen3 data platform that enables the interoperation and creation of cloud-based data resources. Compared to on-premises infrastructure, cloud storage is inexpensive and readily available with automatic backups, and secure analytics in the cloud are easily enabled on large datasets containing protected health information.